POTENSI Centrocema pubescence DAN Calopogonium mucunoidesSEBAGAI PAKANKOMBINASI RUMPUT (STUDI KASUS DI KAMPUNG WASUR) - Irine Ike Praptiwi; Yenni Pentauli Pasaribu; Diana Sri Susanti (Universitas Musamus, Merauke, Papua, 2013)
This research aims to know the potency of Centrocema pubescence andCalopogonium mucunoides which is located in Wasur area as ruminant feed. The research was conducted in Wasur village, Meraukeregency and laboratory of the animal feed nutrition and PAU in Bogor Agricultural University.Sample which used in this research arefeeding grass of leguminosa which grow crept and other wild feeding grass growing around area of Wasur especially settlement of society of local.The results revealed thatthe dominate of Centrocema pubescence and Calopogonium mucunoidesin Wasur area were (34.79%) and (31.69%), respectively.The carriying capacity for small ruminant (goat/sheep) in Wasur area that dominated with Centrocema pubescenceand Calopogonium mucunoides 3,63 AU/ha/month. Calopogonium mucunoidescould not be given forruminant as single feed because its saponin content is more than 3%.